Finasteride and its potential for the treatment of female pattern hair loss: Evidence to date - Wimolsiri Iamsumang (2020)
© 2020 Iamsumang et al. The currently approved treatment for female pattern hair loss (FPHL) includes topical minoxidil administration; however, this treatment fails to achieve hair regrowth in some patients. Finasteride, a selective 5α-reductase inhibitor (5-ARI), may be considered as an alternative treatment. However, because of its potential teratogenic effects, clinical studies and use of finasteride for FPHL are limited. In this review, we aim to summarize the literature regarding the pharmacology, clinical efficacy, and adverse effects of oral finasteride for the treatment of FPHL and to provide novel therapeutic options including topical finasteride and dutasteride, a new generation 5-ARI, for the treatment of FPHL.